Construindo relações de inclusão/exclusão na sala de aula de química: histórias sociais e singulares - Maria de Fatima Cardoso Gomes (2004)
This paper results from the research carried out in Chemistry classes in two groups, one in a federal and the other in a private secondary school during 2000 and 2001. Our aim was to understand the inclusion/exclusion relation which occurred in learning teaching processes in secondary school Chemistry classes. It analyzes processes through which students make meaning and learn in school and in Chemistry classes. It therefore analyzes inclusion and exclusion stories constructed in Chemistry classes interaction and actions. There were two inclusion/exclusion potentials in the two classrooms: what counted as Chemistry knowledge and what counted as a pedagogical proposal. The pedagogical proposal was based on students´ being organized in small groups so that they could talk to and about Chemistry under teachers´ coordination. Organization in small groups proved to be the strongest inclusion factor from the students´ point of view, i. e., the pedagogical feature which most included all the students in both classrooms. This research discusses both inclusion and exclusion because we regard them as two sides of the same coin. In addition, inclusion is not dealt with abstractly, but as inclusion and exclusion stories, through nine Chemistry students´ school anecdotes. Students´ peculiarities, constructed in the group, were taken into account. Gender, ethnicity / race, social class and school stories were also considered. Contrastive tables between pairs of students were made based on the data collected through interviews, questionnaires, classroom interactions and actions. There were no conclusions that either gender, ethnicity/race, social class or school history alone could explain inclusion/exclusion processes. Issues related to peculiarities of research subjects are still to be further understood by educational researchers, such as myself.